Determinan Profitabilitas Perusahaan Properti Dan Real Estate Di Indonesia - Razita Izza Istiqomah; Wida Purwidianti; Hengky Widhiandono; Ika Yustina Rahmawati (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
Fluctuations in the profitability of the property and real estate sector in the 2022-2024 period demand more adaptive financial strategies. This study evaluates the role of operational efficiency and funding structure in determining the financial performance of 46 property and real estate companies listed on the Indonesia Stock Exchange. The novelty of this study lies in the examination of capital structure variables, which provides a new perspective on the effectiveness of debt under dynamic interest rate conditions. The findings indicate that accelerated asset turnover (Total Asset Turnover) and large company scale (Size) are the main drivers of increased profitability. Conversely, high reliance on debt (Capital Structure) actually becomes a financial burden that significantly depresses net income. The level of liquidity (Current Ratio) does not guarantee effective profit generation, indicating that excessive cash management without productive investment does not add value. Overall, this model is able to explain 80.8% of the variation in profitability. These results strengthen the relevance of signaling theory and pecking order theory and provide strategic guidance for management to prioritize asset efficiency over increasing debt burdens to maintain business sustainability.